Study on the Enhancement of Energy Storage Mechanism for Phase Change Materials by High Porosity Metal Foams: Numerical Simulation - Liu, Ming; Wang, Zilong; Zhang, Hua; Zhu, Liucan; Zhu, Hua; lv, Nan (Recent Patents on Mechanical Engineering, 2025)
IntroductionThe findings of the study elucidated that as the porosity of copper foam diminished, the internal average temperature of the composite phase change material increased, concurrent with a reduction in the maximum average temperature differential and an enhancement in temperature homogeneity between the heating interface and the copper composite phase change material. Patent methods and models were applied to investigate this effect.MethodsUnder the filling rate of this experiment, the heat transfer mechanism of copper composite phase change materials (CPCMs) was mainly heat conduction.ResultsWith the increase of porosity, the melting time of phase change materials shortened, and the change of natural convection ratio was more obvious. At the same melting time, the porosity decreased, and the pressure drop increased.ConclusionWhen the porosity was 94% and 96%, the pressure drop was 1425.34 Pa/m and 1222.65 Pa/m, respectively, which was 37.01% and 17.53% higher than that when the porosity was 98%.
Keywords: numerical simulation